2023
DOI: 10.1021/acs.inorgchem.3c00479
|View full text |Cite
|
Sign up to set email alerts
|

Molar-Ratio-Dependent Coordination Assembly of Organoiridium(III)-Octatungstate Complexes in Aqueous Solution

Abstract: We scrutinized the speciation of Cp*Ir-containing tungsten oxide clusters (Cp* is pentamethylcyclopentadienyl anion) in aqueous mixtures of [(Cp*IrCl)2(μ-Cl)2] and Na2WO4 in varying molar ratios. 1H nuclear magnetic resonance (NMR) spectroscopy revealed the formation of three distinct Cp*Ir–polyoxotungstate species in the reaction solution, and they were isolated as Na4[(Cp*Ir)2(μ-OH)3]2[(Cp*Ir)2H2W8O30] (1), [(Cp*Ir)2(μ-OH)3]2[(Cp*Ir)2{Cp*Ir(OH2)}2H2W8O30] (2), and [(Cp*Ir)2{Cp*Ir(OH2)}2{Cp*Ir(OH2)2}2H2W8O30]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…The corresponding SSNMR spectra are essentially the same. These NMR and metrical data are consistent with previously reported Ir-NH 2 Me complexes. , …”
supporting
confidence: 92%
“…The corresponding SSNMR spectra are essentially the same. These NMR and metrical data are consistent with previously reported Ir-NH 2 Me complexes. , …”
supporting
confidence: 92%
“…As shown in Figure a, 1 consists of a tetra-(Cp*Ir)-grafted octatungstate [{Cp*Ir­(OH 2 )} 2 (Cp*Ir) 2 H 2 W 8 O 30 ] 2– (Ir 4 W 8 , see Scheme ) anionic core with two additional {Ag­(OH 2 ) 2 } + fragments, and hence, 1 is a charge-neutral complex. The Ir 4 W 8 anion has been reported by Niu et al and recently by us and is made up of cubane-type {Cp*IrW 3 O 12 (OH)} 5– , bridging cis -{WO 2 } 2+ , and dangling {Cp*Ir­(OH 2 )} 2+ fragments; the {Cp*IrW 3 O 12 (OH)} 5– fragment is also the building units in 2-Co , 2-Ni , 3-Cr , 3-Fe , and 3-In , see below.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that the reaction of [(Cp*IrCl) 2 (μ-Cl) 2 ] and Na 2 WO 4 in aqueous solutions produces a highly nucleophilic octatungstate [{W 3 O 12 (OH)} 2 (WO 2 ) 2 ] 10– anion, which is capped by multiple {Cp*Ir} 2+ fragments (Scheme ). Our question was whether the {Cp*Ir} 2+ cations are substitutable to Werner-type transition-metal aquo cations. Herein, we demonstrate that the addition of Ag + , Co 2+ , Ni 2+ , and M 3+ (M = Cr, Fe, or In) cations into the aqueous solution of Cp*Ir-octatungstate clusters produces [{Ag­(OH 2 ) 2 } 2 ­{Cp*Ir­(OH 2 )} 2 ­{Cp*IrW 3 O 12 (OH)} 2 ­(WO 2 ) 2 ] ( 1 ), Co 1.5 K 0.8 Na 0.2 ­[{ trans -Co­(OH 2 ) 2 }­{Cp*IrW 3 O 12 (OH)} 2 ­(WO 2 ) 1.3 ­{ cis -Co­(OH 2 ) 2 } 0.7 ] ( 2-Co ), Ni 0.2 K 1.4 Na 0.2 ­[{Ni­(OH 2 ) 4 } 2 ­{Cp*IrW 3 O 12 (OH)} 2 ­(WO 2 ) 1.1 ­{ cis -Ni­(OH 2 ) 2 } 0.9 ] ( 2-Ni ), and [{M­(OH 2 ) 4 } 2 ­{Cp*IrW 3 O 12 (OH)} 2 ­{ cis -M­(OH 2 ) 2 } 2 ]­(NO 3 ) 2 (M = Cr, 3-Cr ; Fe, 3-Fe ; or In 3-In ), respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 99%